Current state and positive impact of hospital‐based blood donor centers in the United States. Issue 2 (14th November 2021) - Jacquot, Cyril; Mei, Zhen; Khan, Jenna; Dunbar, Nancy; Delaney, Meghan; Ziman, Alyssa
Abstract: Background: The COVID‐19 pandemic has brought tremendous challenges to the United States blood supply. Decreased collections have caused blood product shortages. The number of hospital‐based donor centers (HBDCs) has decreased in the past decades, but they provide important support to their hospital systems. Materials/Methods: We identified 79 active HBDCs through an information request to the FDA. These centers were invited to participate in a survey about their activities, blood product collections, and perceived value. Results: Thirty‐six centers responded (46% response rate). The centers represented a wide range of states and geographic settings. Whole blood collection was most common, but some respondents also prepared specialized products such as COVID‐19 convalescent plasma and pathogen‐reduced platelets. Positive impacts of HBDCs included inventory availability, cost‐effectiveness/savings, community outreach, supporting special patient populations, and collecting specialty products. All respondents anticipate at least stable operations, if not growth, in the future. Conclusion: HBDCs continue to be valuable assets in addressing emerging patient transfusion needs. Their unique offerings are tailored to the populations their hospitals support, and demonstrate the value in having the collection infrastructure in place to rapidly respond to critical shortages. This survey provides benchmark data about a broad group of HBDCs including products prepared, inventory self‐sufficiency levels, and reasons for positive impact.